3D Proton Transfer Augments Bio‐Photocurrent Generation. (18th March 2015) - Rao, Siyuan; Guo, Zhibin; Liang, Dawei; Chen, Deliang; Li, Yuan; Xiang, Yan
<x xml:space="preserve">Abstract</x> An enhancement of the photocurrent is achieved in a biohybrid nanocomposite consisting of nanovesicle reconstituted proteorhodopsin and potassium phosphotungstate nanoparticles. With the observation of an accelerated protein photocycle and elevated proton conductivity, this improvement of the photoelectric performance is attributed to the construction of a 3D proton‐transfer framework. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>